ROLE OF URODYNAMIC STUDIES IN EVALUATION OF LOWER URINARY TRACT SYMPTOMS: Urodynamic Studies - Niaz, Waqar Azim; Alvi, Sarwar; Hameed, Nazli (Pakistan Armed Forces Medical Journal, 2009)
Objectives: To emphasize the role of urodynamic studies in the evaluation of lower urinary tract symptoms and to describe the technique and report results of tracings from a urodynamic centre in a tertiary care settings. Study Design: Descriptive Study Place and Duration of study: This study was carried out at Armed Forces Institute of Urology, Rawalpindi, over thirty months from January 2003 to June 2005. Patients and Methods: Sixty seven patients referred to the urodynamic centre of AFIU, Rawalpindi with complaints of urinary incontinence or voiding disorders were evaluated with conventional urodynamic tests. During cystometry, the detrusor activity, bladder sensation, bladder capacity and bladder compliance were measured with simultaneous urinary flow measurement in those who were able to void. Results were grouped into eight different types of urodynamic diagnoses. Results: There were 51 females (76%) and 16 males (24%) patients. Majority of patients (48%) were in age group of 20 – 50 years. Ages ranged from 5 – 84 with a mean of 41.3 ± 17.3 years. Majority of the patients found to have neuropathic bladder (25.3%) followed by patients with pure stress incontinence (23.9%). In 38 female patients who presented with urinary incontinence, majority of them i.e. 16 (42.1%) were found to have pure stress incontinence on urodynamic evaluation while 11 (28.9%) patients had normal cystometric findings and 5 patients (13.1%) had hypersensitive cystometrogram signifying sensory urge incontinence while motor urge incontinence implying detrusor instability occurred in 1 patient(2.7%) . Conclusion: Urodynamic studies are useful in evaluation of lower urinary tract symptoms not responding to conventional medical treatment as they help clinician in identifying the underlying causes for the symptoms, and to quantify the related pathophysiological processes. Treatment of the underlying pathophysiology facilitates better treatment of symptoms.